Automatically Minded: A Research of Motor and Shared Intention - Diah Febri Utami; Anjar Tri Wibowo; Muhammad Singgih Gumiwang (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2023)
A purposive account of action must draw to propositional attitude states like intentions, beliefs, and desires as well as to motor representations, i.e., non-propositional forms that denote, among other things, action outcomes as specified kinematic features of bodily motions. It raises the puzzle of how these two distinct types of states successfully coordinate, especially in the automatic movements cases. By using a semi-systematic literature methodology, we examine this interface matter. First, we expand on the nature of intention and its functionality. Second, we characterize motor representations in explaining intentional action and raising the complex of automatic motions. The differences in representational format challenge the interface of theory. We argue that though the low-level motor lacks cognitively penetrable, it processes such perceptual abilities regarding knowledge-involving based on sensitivity. The notion is quite interesting when it's attached to the social realm. Consider one who 'reflexively' helps her neighbor by bringing her piano; after seeing that the neighbor is struggling enough to get it downstairs. The case goes to the issue of collective intentionality as the power of minds to be jointly directed at objects, states of affairs, matters of fact, values, or goals. The question is, what is the explanatory relevance of we-intentions? Is that possible that I have an alternative intention to the 'we' while still satisfying the we-intention? Should the intentions of 'I' and 'you' be deducible from the intentions of 'we'? In the last discussion, we suggest 'meaning' beside the self-referential as a hint for the case of collective intentionality.